Răspuns :
{a;b} d.p. {11;3}
[tex] \frac{a}{11} = \frac{b}{3} = k [/tex]
a=11k, b=3k
a:b=3 (r.24)
a=3b+24
3*3k+24=11k
9k+24=11k
11k-9k=24
2k=24
k=24:2
k=12
a=11*k ⇒ a=11*12 ⇒ a=132
b=3*k ⇒ b=3*12 ⇒ b=36
Sper ca te-am ajutat.
k - factorul de proportionalitate si * - inmultire.
[tex] \frac{a}{11} = \frac{b}{3} = k [/tex]
a=11k, b=3k
a:b=3 (r.24)
a=3b+24
3*3k+24=11k
9k+24=11k
11k-9k=24
2k=24
k=24:2
k=12
a=11*k ⇒ a=11*12 ⇒ a=132
b=3*k ⇒ b=3*12 ⇒ b=36
Sper ca te-am ajutat.
k - factorul de proportionalitate si * - inmultire.